The Moderating Effect of Integration between ERP and CRM Systems on Organizational Performance - Bani Issa, Wesam; Qutaishat, Fadi (Jordan Journal of Business Administration, 2020)
This research aimed at examining the moderating effect of system integration between Enterprise Resources Planning (ERP) system and organizational performance and between Customer Relationship Management (CRM) system and organizational performance in Jordanian automobile companies. The population of this research consisted of all ERP and CRM users in the targeted companies. The sample of the study was selected using the purposive sampling technique. Furthermore, descriptive and analytical approaches have been used and data was collected through a survey questionnaire that was designed in accordance with the research variables. The research hypotheses were tested using several descriptive and analytical tests, including simple regression and interactive linear regression using the Statistical Package for the Social Sciences (SPSS) software. The results of this research revealed that there was a statistically significant effect of ERP system implementation, CRM system implementation and system integration on the organizational performance in Jordanian automobile companies. In addition, there was a moderating effect (but not statistically significant) of system integration between ERP and CRM systems on organizational performance. Several recommendations were outlined, including that Jordanian automobile companies need to further enhance the implementation of ERP and CRM systems and most importantly to integrate the information of both system types in a way that increases organizational performance.